Application of genome‐editing technology in crop improvement. Issue 1 (16th January 2018) - Ni, Zhe; Han, Qian; He, Yong‐Qiang; Huang, Sheng
Abstract : Background and objectives: Increase in the world population is usually followed by a growing demand for food and increasingly higher requirements for the quality of food. The existing crops may require immediate improvement and optimization in order to adjust to market demands and the deteriorating environment. Findings: Genome‐editing technology, a relatively advanced technology method that appeared in recent years, can accurately edit (i.e., insert, delete, or replace) genes and directionally modify crops by changing the plant's heredity and performance. Conclusions: Currently, some of the modern genome‐editing approaches have been applied rather widely in crop breeding: for example, zinc finger nuclease, transcription activator‐like effector nuclease, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein. Significance and novelty: While reviewing the principles of the above genome‐editing technologies and their research progress in crop improvement, this study will discuss the commercial application and future development of these technologies.